Manajemen Pasien Kejang Demam Kompleks di Ruang Rawat Inap Anak RSUD Cut Meutia Aceh Utara - M. Doli Reza Lubis; Mauliza Mauliza (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Febrile seizures are seizure episodes that occur in association with an elevation in body temperature (rectal temperature >38°C) caused by an extracranial process. Febrile seizures are classified into two types: simple febrile seizures and complex febrile seizures. The World Health Organization (WHO) estimated that in 2019 there were 18.3 million cases of febrile seizures worldwide, with approximately 154,000 resulting in death. This case report discusses a patient, An YZ, a 1 year and 5-month-old female, who was brought to the emergency department of Cut Meutia Hospital with a chief complaint of seizures. The seizures began two days prior to hospital admission, characterized by generalized tonic stiffening and clonic movements involving the entire body. Each episode lasted approximately 5 minutes. The seizures occurred twice, initially at 7:00 PM and subsequently at 9:00 PM. The patient was diagnosed with complex febrile seizures associated with morbilli and very mild microcytic hypochromic anemia due to iron deficiency anemia. Pharmacological management included cefotaxime, ranitidine, ondansetron, paracetamol, ambroxol, cetirizine, diazepam (Stesolid), and vitamin D. After three days of hospitalization, the patient showed clinical improvement and was discharged.